Use Of Anti Hypertension And Factors That Affect The Compliance Of Drinking Anti Hypertension In Hypertension Patients In Cisalak Pasar Depok Health Center - Meiskha Bahar; Hany Yusmaini; Sri Wahyuningsih (Pusat Unggulan Iptek (PUI) Poltekkes Kemenkes Yogyakarta, 2020)
Compliance with treatment is an important factor in the health of hypertensive patients. Compliance is a prerequisite for the effectiveness of hypertension therapy, whereas patient non-compliance with antihypertensive drugs is one of the main factors in the failure of therapy. There are several factors that influence medication adherence and some basic principles of therapy that need to be considered to reach the target of therapy and reduce complications of hypertension. Hypertension sufferers in the Cisalak Pasar Community Health Center are quite numerous, they are generally elementary school and not schooled (74.2%). Kidney complications and a combination of heart and kidney are also quite large, which is 40%. This study aims to determine the pattern of antihypertensive administration and the relationship of age, education level, degree of hypertension, complications and type of therapy with the level of adherence to taking medication for hypertensive patients at the Cisalak Pasar Community Health Center. The research design used in this study was a descriptive cross-sectional. The subjects of the study were essential hypertension patients at the Cisalak Pasar Health Center, Depok who met the inclusion and exclusion criteria. The results of this study are that the pattern of antihypertensive administration is in accordance with JNC 8, there is no relationship between age, education level, hypertension degree and the number of drugs taken with medication compliance, and there is a relationship between the presence or absence of complications with medication compliance